Orchid diversity in a logging concession in Tabalong District, South Kalimantan, Indonesia - DWI MURTI PUSPITANINGTYAS (Society for Indonesian Biodiversity, 2020)
Abstract. Puspitaningtyas DM. 2020. Orchid diversity in a logging concession in Tabalong District, South Kalimantan, Indonesia. Biodiversitas 21: 5455-5464. Borneo is the third largest island in the world, and considered the